Older infants' social learning behavior under uncertainty is modulated by the interaction of face and speech processing - Dillmann, Julia; Evertz, Judith; Krasotkina, Anna; Clerc, Olivier; Pascalis, Olivier; Schwarzer, Gudrun; Justus Liebig University Giessen (My University, 2024)
The origin of face or language influences infants' perceptual processing and social learning behavior. However, it remains unclear how infants' social learning behavior is affected when both information are provided simultaneously. Hence, the current study investigated whether and how infants' social learning in terms of gaze following is influenced by face race and language origin of an interaction partner in an uncertain situation. Our sample consisted of 91 Caucasian infants from German speaking families. They were divided into 2 age groups: Younger infants were 5- to 8-month-old (n = 46) and the older infants 11- to 20-month-old (n = 45). We used a modified online version of the gaze following paradigm by Xiao and colleagues by varying face race (Caucasian, and Asian faces) and language (German and French) of a female actor. We recorded infants looking behavior via webcam and coded it offline. Our results revealed that older but not younger infants were biased to follow the gaze of own-race adults speaking their native language. Our findings show that older infants are clearly influenced by adults' ethnicity and language in social learning situations of uncertainty.
Keywords: ddc:150